Procedural requirements for administrative limits to property rights - Conticelli, Martina, 1974-; Perroud, Thomas, 1978- (Oxford : Oxford University Press, 2022)
Administrative law permeates all areas of law, and this series focuses on its role both regionally and globally. This volume addresses one of the most traditional sets of procedures, namely the exercise of public powers affecting property rights. It provides a synchronic comparison of legal systems across the EU, US, and regimes beyond the State.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Property; Comparative law; Law; Laws of specific jurisdictions & specific areas of law